SHALLOW SUBSURFACE STRUCTURES AND QUATERNARY DEFORMATIONS ON THE EASTERNMOST MATANO FAULT, INDONESIA, REVEALED BY ELECTRICAL RESISTIVITY TOMOGRAPHY - Adi Patria; Muhammad Hanif; Danny Hilman Natawidjaja; Mudrik Rahmawan Daryono (Rudarsko-geološko-naftni Zbornik)
In active fault studies, electrical resistivity tomography (ERT) with wide electrode spacing (10 m) and fewer than 60 electrodes is typically utilized. However, this configuration limits the ability of ERT to resolve detailed geological information, such as fault geometry and motion, small-scale offset, and thickness of Quaternary layers. High-resolution electrical resistivity tomography (ERT) with narrow electrode spacing (1.5‒5 m) and 112 electrodes offers an opportunity to uncover finer geological information. This study combines ERT measurements with geological data from trenches and field observations to investigate the subsurface structures and Quaternary deformation on the easternmost Matano fault. On ERT sections, the easternmost Matano fault is characterized by deformed resistivity layers and resistivity contrasts. The subsurface fault structures dip steeply and indicate reverse and normal motions for the vertical component, with the displacement related to the Quaternary faulting ranging from 3 to 26 m. Notably, fault structures on ERT sections are not necessarily expressed by geomorphic features, suggesting obscured tectonic features. This study demonstrates the reliability of high-resolution electrical resistivity tomography (ERT) in unveiling geological information, such as fault location and geometry, fault vertical motions, buried fault structures, small-scale vertical offsets, stratigraphy, and Quaternary sediment thickness, which are essential for seismic hazard assessment.